Blood Oxygen Depletion Is Independent of Dive Function in a Deep Diving Vertebrate, the Northern Elephant Seal - Meir, Jessica U. (Public Library of Science, 2013)
Although energetics is fundamental to animal ecology, traditional methods of determining metabolic rate are neither direct nor instantaneous. Recently, continuous blood oxygen (O(2)) measurements were used to assess energy expenditure in diving elephant seals (Mirounga angustirostris), demonstrating that an exceptional hypoxemic tolerance and exquisite management of blood O(2) stores underlie the extraordinary diving capability of this consummate diver. As the detailed relationship of energy expenditure and dive behavior remains unknown, we integrated behavior, ecology, and physiology to characterize the costs of different types of dives of elephant seals. Elephant seal dive profiles were analyzed and O(2) utilization was classified according to dive type (overall function of dive: transit, foraging, food processing/rest). This is the first account linking behavior at this level with in vivo blood O(2) measurements in an animal freely diving at sea, allowing us to assess patterns of O(2) utilization and energy expenditure between various behaviors and activities in an animal in the wild. In routine dives of elephant seals, the blood O(2) store was significantly depleted to a similar range irrespective of dive function, suggesting that all dive types have equal costs in terms of blood O(2) depletion. Here, we present the first physiological evidence that all dive types have similarly high blood O(2) demands, supporting an energy balance strategy achieved by devoting one major task to a given dive, thereby separating dive functions into distinct dive types. This strategy may optimize O(2) store utilization and recovery, consequently maximizing time underwater and allowing these animals to take full advantage of their underwater resources. This approach may be important to optimizing energy expenditure throughout a dive bout or at-sea foraging trip and is well suited to the lifestyle of an elephant seal, which spends > 90% of its time at sea submerged making diving its most “natural” state.